ASPECTS OF DIABETES MELLITUS - Mamaraimov I; Subkhanov S; Sobirzhonovna Kurbanova (Western European Studies, 2024)
In enokrinologii diabetes has a special place because it has a lot of complications and therefore in our work revealed aspects of his on the basis of literary analysis.
Keywords: complication; prevalence; aspects; cardiac pathology